2017
DOI: 10.1111/dom.12896
|View full text |Cite
|
Sign up to set email alerts
|

Scriptaid enhances skeletal muscle insulin action and cardiac function in obese mice

Abstract: Aim:To determine the effect of Scriptaid, a compound that can replicate aspects of the exercise adaptive response through disruption of the class IIa histone deacetylase (HDAC) corepressor complex, on muscle insulin action in obesity. Materials and methods:Diet-induced obese mice were administered Scriptaid (1 mg/kg) via daily intraperitoneal injection for 4 weeks. Whole-body and skeletal muscle metabolic phenotyping of mice was performed, in addition to echocardiography, to assess cardiac morphology and funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 38 publications
1
16
0
Order By: Relevance
“…However, this disruption could be caused by the early and long treatment period used, which included gastrulation (5-72 hpf ). HC toxin and scriptaid have recently been shown to enhance glucose uptake and metabolism in mouse skeletal muscle (Tan et al, 2015;Gaur et al, 2017). However, these studies only focused on mechanisms downstream of insulin.…”
Section: Discussionmentioning
confidence: 99%
“…However, this disruption could be caused by the early and long treatment period used, which included gastrulation (5-72 hpf ). HC toxin and scriptaid have recently been shown to enhance glucose uptake and metabolism in mouse skeletal muscle (Tan et al, 2015;Gaur et al, 2017). However, these studies only focused on mechanisms downstream of insulin.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity-induced decreases in adiponectin led to decreased insulin sensitivity, but increased circulating insulin levels (Kadowaki et al, 2006;Gaur et al, 2017). Increased insulin levels inhibit AMPK activity in muscle and thereby slow fibre type expression (Valentine et al, 2014).…”
Section: Consequences Of Obesity-induced Decreases In Adiponectin Andmentioning
confidence: 99%
“…Because previous studies demonstrated that Scriptaid induces muscle-adaptive responses by increasing metabolic genes' expression (14,17), lipid oxidation, and glucose utilization, we sought to examine whether Scriptaid stimulates metabolism in osteocytes. Ocy454-12H cells, a clonal osteocytic cell line, were selected for their high sclerostin expression compared with the original Ocy454 cells.…”
Section: Scriptaid and Pth-regulated Expression Of Metabolic Genes In An Osteocytic Cell Line (Ocy454-12h)mentioning
confidence: 99%